(untitled) (Eurasian Journal of Engineering and Technology, 2023)
The purpose of scientific research is a comprehensive, reliable study of an object, process or phenomenon; their structure, connections and relations based on the principles and methods of cognition developed in science, as well as obtaining and introducing into production (practice) results that are useful for humans. Any scientific research has its own object and subject. The object of scientific research is a material or ideal system